CHEOPS geometric albedo of the hot Jupiter HD 209458 b - Brandeker, A.; Davies, M.B.; Wolter, D. (Astronomy and Astrophysics, 2022)
We report the detection of the secondary eclipse of the hot Jupiter HD 209458 b in optical/visible light using the CHEOPS space telescope. Our measurement of 20.4−3.3+3.2 parts per million translates into a geometric albedo of Ag = 0.096 ± 0.016. The previously estimated dayside temperature of about 1500 K implies that our geometric albedo measurement consists predominantly of reflected starlight and is largely uncontaminated by thermal emission. This makes the present result one of the most robust measurements of Ag for any exoplanet. Our calculations of the bandpass-integrated geometric albedo demonstrate that the measured value of Ag is consistent with a cloud-free atmosphere, where starlight is reflected via Rayleigh scattering by hydrogen molecules, and the water and sodium abundances are consistent with stellar metallicity. We predict that the bandpass-integrated TESS geometric albedo is too faint to detect and that a phase curve of HD 209458 b observed by CHEOPS would have a distinct shape associated with Rayleigh scattering if the atmosphere is indeed cloud free.
Number of authors = 77 EID = 85126114426 Article no = L4 Affiliation = Brandeker, A., Department of Astronomy, Stockholm University, AlbaNova University Center, Stockholm, 10691, Sweden Affiliation = Walton, N., Institute of Astronomy, University of Cambridge, Madingley Road, Cambridge, CB3 0HA, United Kingdom Affiliation = Wolter, D., Institute of Planetary Research, German Aerospace Center (DLR), Rutherfordstrasse 2, Berlin, 12489, Germany